UPAYA MENINGKATKAN HASIL BELAJAR KETERAMPILAN MENGGIRING BOLA MELALUI MEDIA PEMBELAJARAN BOLA PLASTIK DI SEKOLAH DASAR - Syamsudin, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe problems discussed in this research is how to improve learning activities dribble with plastic balls on the fifth grade students of SDN 26 Nanga Pinoh Melawi. The purpose of this study was to determine the learning outcome dribbling skills with a plastic ball on the class V students of SDN 26 Nanga Pinoh Melawi. This research uses research